Commentary on the long term athlete development model for British Swimming and the misinformation it propagates - Rushall, B. S. (Swimming Science Bulletin, 2011)
Occasionally in sports, a synthesis of the thoughts and beliefs pervading a sport is revealed. In 2003 that occurred for swimming in Great Britain, when a white paper that was intended to provide guidelines and directions to coaches and administrators was released. The impact of that set of directives was evaluated and published in the International Journal of Sports Science and Coaching (IJSSC; Lang & Light, 2010). While minor quirks and differences occur between the programming content of the major swimming nations, to a large extent, the British production is Swimming Science Bulletin #38 2 representative of the international belief structures of swimming. For this discussion, the content of the plan produced by British Swimming and the added tenets that were included in the journal's commentary articles will be considered to represent the "common" thinking in swimming. This review and reactions illustrate the extent and duration of scientific inquiry that must have been ignored to develop the unfounded and misinformed beliefs that permeate competitive swimming coaching. It will focus on the coaching of pre-pubertal swimmers. Parts of the article: Long Term Athlete Development Model for British Swimming is a Recipe for Confusion Swimming Lore and Misinformation is Still Very Prevalent in High Levels of the Sport Race-pace Work and Judicious Work and Recovery Sets Should Govern the Programming of Training Sets Technique is Under-emphasized or Ignored in Long-term Development Models of Competitive Swimming Psychology is Neglected in LTAD Models